Leadership Practices of Madrasah Principals in the Implementation of the Merdeka Curriculum - Aini Safitri; Amiruddin Siahaan; Mardianto Mardianto (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The purpose of this study is to analyze the leadership of madrasah principals in planning, implementation, and evaluation activities in implementing the Merdeka Curriculum that integrates it with Digital Madrasah innovations then analyze the impact of leadership models and digital innovations in the Merdeka Curriculum on the learning process at State Islamic Junior High School. Methodology: This study uses a qualitative approach with a multi-site study design, which focuses on two state madrasahs in Aceh Tamiang Regency. Data sources include the madrasah principal, deputy head of curriculum, teachers, supervisors, and students. Main Findings: The results of this study offer novelty in the form of mapping two leadership patterns of madrasah principals in implementing the Merdeka Curriculum that integrates digital innovations, namely the reflective-open model at State Islamic Junior High School 1 and the systemic-digital model at State Islamic Junior High School 2 which result in different strategies in planning, implementation, evaluation, and impact. This study formulates a new model in the form of a cultural-pedagogical versus systemic-pedagogical change pathway, as well as a hybrid reflective-digital evaluation model, which overall form the 'Contextualized Digital-Merdeka Leadership' framework as a significant theoretical and practical contribution. Novelty/Originality of this study: The research novelty was formulates a new model in the form of a cultural-pedagogical versus systemic-pedagogical change pathway, as well as a hybrid reflective-digital evaluation model, which collectively form the Contextualized Digital-Merdeka Leadership framework as a significant theoretical and practical contribution previously undiscovered in madrasah leadership studies in Indonesia.